Positive association between a glutathione‐S‐transferase polymorphism and lymphoma in dogs. (29th September 2012) - Ginn, J.; Sacco, J.; Wong, Y. Y.; Motsinger‐Reif, A.; Chun, R.; Trepanier, L. A.
Abstract Glutathione‐S‐transferase enzymes (GSTs) play an important role in the detoxification of environmental carcinogens. Defective GST genotypes are over‐represented in human cancers; in particular, low activity GSTT1 genotypes are risk factors for non‐Hodgkin lymphoma. We hypothesized that defective GSTT1 genotypes would be associated with lymphoma risk in dogs. To address this, we resequenced the exons, splice junctions, and 3′‐UTR of canine GSTT1 in dogs with lymphoma (n = 93) and age‐matched unaffected dogs (n = 86). Of 27 canine GSTT1 variants identified, the I2+28 G>A was significantly associated with lymphoma [odds ratio (OR) 6.26, 95% confidence interval (CI), 1.77–22.2], with the AA genotype found in 18.3% of affected dogs but only 3.5% of controls (P = 0.002). This intronic variant was predicted to perturb GSTT1 mRNA splicing, and may increase lymphoma risk by impairing detoxification of environmental chemicals. Confirmation of this finding in a larger population of dogs may support the inclusion of GSTT1 genotyping in epidemiologic studies of canine lymphoma risk.